Nephrotic syndrome as a complication of chronic graft‐versus‐host disease after allogeneic haemopoietic stem cell transplantation. Issue 6 (3rd June 2016) - Wong, E.; Lasica, M.; He, S. Z.; Bajel, A.; Roberts, A. W.; Mason, K. D.; Ritchie, D. S.; Szer, J.
Abstract : Nephrotic syndrome (NS) is a rare complication following allogeneic haemopoietic stem cell transplantation (allo‐HSCT), with limited current understanding of its pathogenesis. Here, we describe four cases of NS following allo‐HSCT diagnosed at our institutions to identify key clinical and pathological features. In addition, a PubMed search was performed to identify existing reports that were pooled together with our cases for analysis. NS occurred as a late complication following allo‐HSCT, with median onset 19.5 months after transplant (range: 3.9–84 months). The most common histopathology observed was membranous nephropathy; however, cases of minimal change disease have also been reported. There is a high incidence of prior extra‐renal graft‐versus‐host disease (GvHD), with all four of our cases and 82% of published cases having prior GvHD. Glucocorticosteroids are the most common treatment, with variable degrees of response. Responses to immunosuppression with calcineurin inhibitors and rituximab have been described in steroid‐refractory cases.